Characterisation of tyre wear particle transport from road runoff to sea in coastal environments - Florence N.F. Parker-Jurd; Geoffrey D. Abbott; Daniel C. Conley; Cijo M. Xavier; Florian Pohl; Richard C. Thompson (Marine Pollution Bulletin, 2025)

The Holocene silicon biogeochemistry of Yellowstone Lake, USA - Petra Zahajská; Patrick J. Frings; François Gaspard; Sophie Opfergelt; Johanna Stadmark; Sherilyn C. Fritz; Rosine Cartier; Daniel J. Conley (Quaternary Science Reviews, 2023)

A Global Ocean Oxygen Database and Atlas for Assessing and Predicting Deoxygenation and Ocean Health in the Open and Coastal Ocean - Marilaure Grégoire; Véronique Garçon; Hernan Garcia; Denise Breitburg; Kirsten Isensee; Andreas Oschlies; Maciej Telszewski; Alexander Barth; Henry C. Bittig; Jacob Carstensen; Thierry Carval; Fei Chai; et al. (Frontiers in Marine Science, 2021)
In this paper, we outline the need for a coordinated international effort toward the building of an open-access Global Ocean Oxygen Database and ATlas (GO 2 DAT) complying with the FAIR principles (Findable, Accessible, Interoperable, and Reusable). GO 2 DAT will combine data from the coastal and open ocean, as measured by the chemical Winkler titration method or by sensors (e.g., optodes, electrodes) from Eulerian and Lagrangian platforms (e.g., ships, moorings, profiling floats, gliders, ships of opportunities, marine mammals, cabled observatories). GO 2 DAT will further adopt a community-agreed, fully documented metadata format and a consistent quality control (QC) procedure and quality flagging (QF) system. GO 2 DAT will serve to support the development of advanced data analysis and biogeochemical models for improving our mapping, understanding and forecasting capabilities for ocean O 2 changes and deoxygenation trends. It will offer the opportunity to develop quality-controlled data synthesis products with unprecedented spatial (vertical and horizontal) and temporal (sub-seasonal to multi-decadal) resolution. These products will support model assessment, improvement and evaluation as well as the development of climate and ocean health indicators. They will further support the decision-making processes associated with the emerging blue economy, the conservation of marine resources and their associated ecosystem services and the development of management tools required by a diverse community of users (e.g., environmental agencies, aquaculture, and fishing sectors). A better knowledge base of the spatial and temporal variations of marine O 2 will improve our understanding of the ocean O 2 budget, and allow better quantification of the Earth’s carbon and heat budgets. With the ever-increasing need to protect and sustainably manage ocean services, GO 2 DAT will allow scientists to fully harness the increasing volumes of O 2 data already delivered by the expanding global ocean observing system and enable smooth incorporation of much higher quantities of data from autonomous platforms in the open ocean and coastal areas into comprehensive data products in the years to come. This paper aims at engaging the community (e.g., scientists, data managers, policy makers, service users) toward the development of GO 2 DAT within the framework of the UN Global Ocean Oxygen Decade (GOOD) program recently endorsed by IOC-UNESCO. A roadmap toward GO 2 DAT is proposed highlighting the efforts needed (e.g., in terms of human resources).

Recovery from multi‐millennial natural coastal hypoxia in the Stockholm Archipelago, Baltic Sea, terminated by modern human activity - Niels A. G. M. van Helmond; Bryan C. Lougheed; Annika Vollebregt; Francien Peterse; Guillaume Fontorbe; Daniel J. Conley; Caroline P. Slomp (Limnology and Oceanography, 2020)
Enhanced nutrient input and warming have led to the development of low oxygen (hypoxia) in coastal waters globally. For many coastal areas, insight into redox conditions prior to human impact is lacking. Here, we reconstructed bottom water redox conditions and sea surface temperatures (SSTs) for the coastal Stockholm Archipelago over the past 3000 yr. Elevated sedimentary concentrations of molybdenum indicate (seasonal) hypoxia between 1000 b.c.e. and 1500 c.e . Biomarker‐based (TEX 86 ) SST reconstructions indicate that the recovery from hypoxia after 1500 c.e. coincided with a period of significant cooling (∼ 2°C), while human activity in the study area, deduced from trends in sedimentary lead and existing paleobotanical and archeological records, had significantly increased. A strong increase in sedimentary lead and zinc, related to more intense human activity in the 18 th and 19 th century, and the onset of modern warming precede the return of hypoxia in the Stockholm Archipelago. We conclude that climatic cooling played an important role in the recovery from natural hypoxia after 1500 c.e. , but that eutrophication and warming, related to modern human activity, led to the return of hypoxia in the 20 th century. Our findings imply that ongoing global warming may exacerbate hypoxia in the coastal zone of the Baltic Sea.

Comparison of HF Radar Fields of Directional Wave Spectra Against In Situ Measurements at Multiple Locations - Guiomar Lopez; Daniel C. Conley (Journal of Marine Science and Engineering, 2019)
The coastal zone hosts a great number of activities that require knowledge of the spatial characteristics of the wave field, which in coastal seas can be highly heterogeneous. Information of this type can be obtained from HF radars, which offer attractive performance characteristics in terms of temporal and spatial resolution. This paper presents the validation of radar-derived fields of directional wave spectra. These were retrieved from measurements collected with an HF radar system specifically deployed for wave measurement, using an established inversion algorithm. Overall, the algorithm reported accurate estimates of directional spectra, whose main distinctive characteristic was that the spectral energy was typically spread over a slightly broader range of frequencies and directions than in their in situ-measured counterparts. Two errors commonly reported in previous studies, namely the overestimation of wave heights and noise related to short measurement periods, were not observed in our results. The maximum wave height recorded by two in situ devices differed by 30 cm on average from the radar-measured values, and with the exception of the wave spreading, the standard deviations of the radar wave parameters were between 3% and 20% of those obtained with the in situ datasets, indicating the two were similarly grouped around their means. At present, the main drawback of the method is the high quality signal required to perform the inversion. This is in part responsible for a reduced data return, which did not exceed 55% at any grid cell over the eight-month period studied here.

Paleolimnological records of regime shifts in lakes in response to climate change and anthropogenic activities - Linda Randsalu-Wendrup; Daniel J. Conley; Jacob Carstensen; Sherilyn C. Fritz (Journal of Paleolimnology, 2016)

Combining limnology and palaeolimnology to investigate recent regime shifts in a shallow, eutrophic lake - Linda Randsalu-Wendrup; Daniel J. Conley; Jacob Carstensen; Lars-Anders Hansson; Christer Brönmark; Sherilyn C. Fritz; Preetam Choudhary; Joyanto Routh; Dan Hammarlund (Journal of Paleolimnology, 2014)

Hypoxia in the Baltic Sea: Biogeochemical Cycles, Benthic Fauna, and Management - Jacob Carstensen; Daniel J. Conley; Erik Bonsdorff; Bo G. Gustafsson; Susanna Hietanen; Urzsula Janas; Tom Jilbert; Alexey Maximov; Alf Norkko; Joanna Norkko; Daniel C. Reed; Caroline P. Slomp; et al. (Ambio, 2014)

Ecological Regime Shifts in Lake Kälksjön, Sweden, in Response to Abrupt Climate Change Around the 8.2 ka Cooling Event - Linda Randsalu-Wendrup; Daniel J. Conley; Jacob Carstensen; Ian Snowball; Catherine Jessen; Sherilyn C. Fritz (Ecosystems, 2012)

A welcome can of worms? Hypoxia mitigation by an invasive species - Joanna Norkko; Daniel C. Reed; Karen Timmermann; Alf Norkko; Bo G. Gustafsson; Erik Bonsdorff; Caroline P. Slomp; Jacob Carstensen; Daniel J. Conley (Global Change Biology, 2012)
Invasive species and bottom‐water hypoxia both constitute major global threats to the diversity and integrity of marine ecosystems. These stressors may interact with unexpected consequences, as invasive species that require an initial environmental disturbance to become established can subsequently become important drivers of ecological change. There is recent evidence that improved bottom‐water oxygen conditions in coastal areas of the northern Baltic Sea coincide with increased abundances of the invasive polychaetes M arenzelleria spp. Using a reactive‐transport model, we demonstrate that the long‐term bioirrigation activities of dense M arenzelleria populations have a major impact on sedimentary phosphorus dynamics. This may facilitate the switch from a seasonally hypoxic system back to a normoxic system by reducing the potential for sediment‐induced eutrophication in the upper water column. In contrast to short‐term laboratory experiments, our simulations, which cover a 10‐year period, show that M arenzelleria has the potential to enhance long‐term phosphorus retention in muddy sediments. Over time bioirrigation leads to a substantial increase in the iron‐bound phosphorus content of sediments while reducing the concentration of labile organic carbon. As surface sediments are maintained oxic, iron oxyhydroxides are able to persist and age into more refractory forms. The model illustrates mechanisms through which M arenzelleria can act as a driver of ecological change, although hypoxic disturbance or natural population declines in native species may be needed for them to initially become established. Invasive species are generally considered to have a negative impact; however, we show here that one of the main recent invaders in the Baltic Sea may provide important ecosystem services. This may be of particular importance in low‐diversity systems, where disturbances may dramatically alter ecosystem services due to low functional redundancy. Thus, an environmental problem in one region may be either exacerbated or alleviated by a single species from another region, with potentially ecosystem‐wide consequences.

Caribbean hydrological variability during the Holocene as reconstructed from crater lakes on the island of Grenada - Sherilyn C. Fritz; Svante Björck; Catherine A. Rigsby; Paul A. Baker; Amy Calder‐Church; Daniel J. Conley (Journal of Quaternary Science, 2011)
Contemporary precipitation patterns in the Caribbean region are spatially variable, and the small number of Holocene paleoclimatic records may not adequately capture patterns of variation in the past. The hydrological history of Grenada was inferred from paleolimnological analyses of sediment cores from two crater lakes on the island. The basins were formed by volcanic activity some time during the Last Termination, but were dry between ca. 13 000 and ca. 7200 cal. a BP. After filling, the lakes were initially very shallow, and sedimentation was interrupted by a hiatus ca. 6300–5500 cal. a BP, followed by deposition of a thick tephra in both sites. After 5500 cal. a BP, lake level shows considerable multi‐centennial variability, superimposed upon a long‐term trend of generally higher lake level after 3200 cal. a BP. The pattern of lake‐level variation in Grenada shows some similarity with other Caribbean paleoclimatic records in terms of the timing of transitions, but differs from several classic studies in the sign of inferred precipitation change. The differences among records may reflect spatially variable precipitation patterns in the past in response to the position of the Intertropical Convergence Zone and to sea surface temperature influences on the trade winds and Caribbean low‐level jet. Copyright © 2011 John Wiley & Sons, Ltd.

Erratum to: Regional areas and widths of the midsagittal corpus callosum among HIV-infected patients on stable antiretroviral therapies - David F. Tate; Mehul Sampat; Jaroslaw Harezlak; Mark Fiecas; Joseph Hogan; Jeffrey Dewey; Daniel McCaffrey; Daniel Branson; Troy Russell; Jared Conley; Michael Taylor; Giovanni Schifitto; et al. (Journal of NeuroVirology, 2011)

Regional areas and widths of the midsagittal corpus callosum among HIV-infected patients on stable antiretroviral therapies - David F. Tate; Mehul Sampat; Jaroslaw Harezlak; Mark Fiecas; Joseph Hogan; Jeffrey Dewey; Daniel McCaffrey; Daniel Branson; Troy Russell; Jared Conley; Michael Taylor; Giavoni Schifitto; et al. (Journal of NeuroVirology, 2011)

Deforestation causes increased dissolved silicate losses in the Hubbard Brook Experimental Forest - DANIEL J. CONLEY; GENE E. LIKENS; DONALD C. BUSO; LOREDANA SACCONE; SCOTT W. BAILEY; CHRIS E. JOHNSON (Global Change Biology, 2008)
Globally significant increases in the riverine delivery of nutrients and suspended particulate matter have occurred with deforestation. We report here significant increases in streamwater transport of dissolved silicate (DSi) following experimental forest harvesting at the Hubbard Brook Experimental Forest, NH, USA. The magnitude of the streamwater response varied with the type of disturbance with the highest DSi export fluxes occurring in the manipulations that left the most plant materials on the soil surface and disturbed the soil surface least. No measurable loss of amorphous silica (ASi) was detected from the soil profile; however, ASi was redistributed within the soil profile after forest disturbance. Mass‐balance calculations demonstrate that some fraction of the DSi exported must come from dissolution of ASi and export as DSi. Land clearance and the development of agriculture may result in an enhanced flux of DSi coupled with enhanced erosion losses of ASi contained in phytoliths.